MANAJEMEN PEMBELAJARAN MATA PELAJARAN TAKHASUS PADA MA TARBIYATUL BANIN DI PEKALONGAN WINONG PATI - Moh Sopi’i; Barowi Barowi; Moh Nasuka (Intelegensia : Jurnal Pendidikan Islam, 2019)
AbstractThis research is aimed to: 1) know how the learning management of takhasus in MA Tarbiyatul Banin Pekalongan Winong Pati. 2) know the supporting factors and inhibiting factors that influence takhasus learning process in MA Tarbiyatul Banin Pekalongan Winong Pati. This research is qualitative. So the obtained data is presented in words and not numerical. Data sources used are premier data sources which gotten exclusively from observation and interview and also secondary data sources which gotten by documents about takhasus learning. Then the data validity is tested by using triangulation. Obtained data is analyzed using 3 steps which are data reduction, data presentation, and verification. From the result of data analysis is obtained that: 1) learning management takhasus consist of planning of learning, organizing of learning, learning implementation, and learning evaluation. 2) takhasus learning process in MA Tarbiyatul Banin Pekalongan Winong Pati is supported by competent teacher, good curriculum, supportable facilities, and good learning management. 3) inhibiting factor of takhasus learning is the variety of students’ background.Keywords: Yellow Book; Learning Management; Takhasus